The Influence of Agricultural Extension Services on the Productivity of Small-Scale Agribusiness Farmers - Wahyuni, Ira (Arbain Publishing, 2025)
This study explores the influence of agricultural extension services on the productivity of small-scale agribusiness farmers through a qualitative literature review. Agricultural extension services play a crucial role in disseminating knowledge, providing technical assistance, and enhancing the skills of farmers, which are essential for improving agricultural productivity. The review synthesizes existing research on the effectiveness of these services, highlighting key factors that contribute to successful outcomes, such as the accessibility of information, the relevance of training programs, and the adaptability of extension methods to local contexts. Furthermore, the study identifies barriers that small-scale farmers face in accessing extension services, including socio-economic constraints and limited infrastructure. The findings suggest that effective agricultural extension services can significantly enhance the productivity of small-scale farmers by promoting sustainable practices, improving resource management, and fostering innovation. This research underscores the need for policymakers and agricultural stakeholders to invest in and strengthen extension services to support small-scale agribusinesses. By addressing the gaps in service delivery and ensuring that farmers receive relevant and timely information, the agricultural sector can achieve greater productivity and sustainability. This study contributes to the broader understanding of the role of agricultural extension services in empowering small-scale farmers and highlights the importance of tailored support to meet their specific needs.